Predictive value of Bayley‐III Motor Index for later motor difficulties in children born extremely preterm. (20th February 2023) - Montgomery, Cecilia; Setänen, Sirkku; Kaul, Ylva Fredriksson; Farooqi, Aijaz; Broström, Lina; Aden, Ulrika; Källén, Karin; Serenius, Fredrik
Abstract: Aim: To investigate the predictive ability of the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley‐III) Motor Index, in children born extremely preterm (<27 gestational weeks) without cerebral palsy. Methods: Children from the EXPRESS study (all extremely preterm births in Sweden, 2004–2007) without neurosensory impairments assessed with Bayley‐III at 2.5 years corrected age and Movement Assessment Battery for Children, Second Edition (MABC‐2), at 6.5 years comprised the eligible study population ( n  = 282). Motor difficulty was defined as MABC‐2 ≤5th percentile. Results: Motor difficulties were found in 57 of 282 children (20.2%) at 6.5 years. The Bayley‐III explained 18.0% of the variance in the MABC‐2 ( p  < 0.001). The area under the receiver operating curve was 0.71 (95% confidence interval 0.64−0.79, p  < 0.001). At a Bayley‐III cut‐off value of 85, sensitivity, specificity and positive and negative predictive values for motor difficulties were 26.3% (15.5–39.7), 92.9% (88.1–95.9), 48.4% (33.0–64.0) and 83.3% (80.9–85.4). Likelihood ratios were inconclusive. Conclusion: The Bayley‐III at 2.5 years corrected age was a modest predictor of motor outcome in children born extremely preterm at 6.5 years, and underestimated the rate of motor difficulties. Children require follow‐up beyond preschool age.